Minimally invasive mastectomy: minimal incisions for better aesthetic quality of breast reconstruction - Costa, M. P. (2012)
Background: Women with a family history of breast cancer who develop this disease are confronted with important situations regarding the increased risk for development of a second cancer in the contralateral breast. Prophylactic contralateral mastectomy (PCM) reduces by approximately 95% the risk for contralateral breast cancer. In spite of an increase in indications for PCM, the technical difficulties are many regarding the accomplishment of these procedures. The aim of this study is to describe the technique of mastectomy with preservation of the nipple-areola complex and a small incision, reducing surgical difficulties and complications attributed to this technique, thus allowing better aesthetic results in breast reconstruction. Methods: Forty-six patients with indications for PCM (28 bilateral) were submitted to minimally invasive mastectomy from March 2005 to November 2007. A small incision in the superior pole of the areola, sufficient to pass a liposuction 4 mm cannula is made. With the help of this cannula, detachment of the skin from the gland tissue is performed. Then a 3.5 to 4.5-cm long incision in the inframammary fold is made. Glandular detachment is completed using cautery in the sub,glandular portion and scissors in the upper breast portion cutting the restraints left by the cannula. The mammary gland tissue is removed through this incision. Results: Seventy-four breasts were operated on. The resected breast mass ranged from 285 g to 475 g. All 43 patients were reconstructed with prostheses. There was no necrosis of the nipple-areola complex or of the skin. Conclusions: This technique is an option for cases of patients with indications for PCM.